IMPLEMENTATION OF PERFORMANCE-BASED BUDGET (ABK) AT THE COMMUNICATION AND INFORMATION DEPARTMENT OF SOUTH KALIMANTAN PROVINCE - Noor Apriliana, Syarifah; Anshar Nur, Muhammad; Tenri Sompa, Andi (International Journal Political, Law, and Social Science, 2022)
In practice, from the results of SAKIP's evaluation of the 2017 Performance Report obtained from the Inspectorate of South Kalimantan Province, the results of the performance evaluation of 14 of 47 SKPD are still in the "Good" category and not "satisfactory". This means that the implementation of the Performance-Based Budget (ABK) which is echoed by the government as a step to realize Good Governance through SAKIP has not run optimally. There are still many funded SKPD activities that are not fully performance-based. This study aims to analyze the implementation of Performance-Based Budgeting (ABK) in the Communication and Information Office of South Kalimantan Province. This research is a qualitative research with descriptive analysis technique. Data were collected through interviews, documentation, and observation. The results show that in its implementation there are still obstacles, such as performance reporting that has not been optimal so that it affects performance appraisal, the quality of human resources is still not optimal even though they have been represented and the responsibility of the official apparatus is still low to complete the tasks that are the main tasks and functions; AND the Office of Communication and Informatics of South Kalimantan Province in 2017 has not taken the main steps for implementing performance-based budgeting in accordance with the guidebook for implementing Performance-based budgeting by the National Planning and Development Agency (BAPPENAS).